Penelitian terhadap Perawatan pada Mesin Press Cap Roller dengan Metode FMEA dan RCM - Harma, Beni; Yetrina, Mutiara; Susriyati; Pebriyanto, Riyan (Universitas Putra Indonesia YPTK Padang, 2024)
Maintenance of production machinery is crucial for maintaining the quality of the production process. At PTPN VI Solok, there is a significant issue with the Close Roll Printing Machine, which plays a vital role in the tea pressing process. This study aims to understand the maintenance requirements of the Press Cap Roller Machine and provide maintenance recommendations using the Failure Mode and Effect Analysis (FMEA) and Reliability Centered Maintenance (RCM) methods. FMEA is utilized to examine and track potential failures, while RCM aims to select, develop, and create effective maintenance strategies. The FMEA analysis revealed that the crankshaft is the predominant cause of failure, with a Risk Priority Number (RPN) value of 17.07%. RCM analysis indicated that the Mean Time To Failure (MTTF) for components ranges between 1433.4 and 1811 hours. Recommendations for improvements include checking the crankshaft rotation to ensure it runs smoothly and performing maintenance according to the schedule. Additionally, regular gearbox inspections are crucial, such as checking oil levels, oil circulation conditions, gearbox area leaks, and replacing the gearbox according to the component's lifespan to maintain optimal performance. Other maintenance suggestions involve direct prevention of failure sources and appropriate maintenance, regular bearing replacements and inspections as per the schedule, and routine checks of electrical current and temperature. The implementation of FMEA and RCM methods is expected to provide more structured and effective solutions for maintenance issues, thereby maintaining the quality of the tea production process. This approach also aims to extend the machine's lifespan and reduce unexpected maintenance costs, thus enhancing the company's operational productivity and efficiency.